A single epidermal stem cell strategy for safe ex vivo gene therapy. Issue 4 (27th February 2015) - Droz‐Georget Lathion, Stéphanie; Rochat, Ariane; Knott, Graham; Recchia, Alessandra; Martinet, Danielle; Benmohammed, Sara; Grasset, Nicolas; Zaffalon, Andrea; Besuchet Schmutz, Nathalie; Savioz‐Dayer, Emmanuelle; Beckmann, Jacques Samuel; Rougemont, Jacques; et al.
<x xml:space="preserve">Abstract</x> First time demonstration of a safe clonal strategy for ex vivo gene therapy before autologous transduced cells are transplanted into patients. Using recessive dystrophic epidermolysis bullosa (RDEB) COL7A1 corrected epidermal cloned stem cells as proof of principle, this strategy proves promising for clinical applications. <boxed-text content-type="graphic" id="emmm201404353-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>